2018
DOI: 10.1007/s11136-017-1775-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health literacy on the quality of life of older patients with long-term conditions: a large cohort study in UK general practice

Abstract: PurposeThe levels of health literacy in patients with long-term conditions (LTCs) are critical for better disease management and quality of life (QoL). However, the impact of health literacy on QoL in older adults with LTCs is unclear. This study examined the association between health literacy and domains of QoL in older people with LTCs, investigating key socio-demographic and clinical variables, as confounders.MethodsA prospective cohort study was conducted on older adults (n = 4278; aged 65 years and over)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 61 publications
7
50
1
2
Order By: Relevance
“…However, in our study, health literacy showed a paradoxical effect, as critical health literacy decreased the likelihood of achieving adequate mental health perception. In accordance with previous research, critical health literacy should predict more positive outcome, such as self-care and HRQoL [24,46,47]. In our study, we reported that patients with higher critical thinking abilities about their chronic treatment (higher levels of critical health literacy) reported lower levels of mental health perception.…”
Section: Discussionsupporting
confidence: 91%
“…However, in our study, health literacy showed a paradoxical effect, as critical health literacy decreased the likelihood of achieving adequate mental health perception. In accordance with previous research, critical health literacy should predict more positive outcome, such as self-care and HRQoL [24,46,47]. In our study, we reported that patients with higher critical thinking abilities about their chronic treatment (higher levels of critical health literacy) reported lower levels of mental health perception.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with results of previous studies of other chronic illnesses in which better personal control and illness perception were associated with higher physical QOL . Better health literacy and knowledge about the disease and its treatment can improve QOL in patients with chronic diseases …”
Section: Discussionsupporting
confidence: 91%
“…Next, a little over two‐thirds of all eligible patients (65%) agreed to take part in this study. This response rate is high compared with the response rates for previous studies using similar methods within chronic care …”
Section: Discussionmentioning
confidence: 65%
“…In contrast, a large cohort study of general practices in the UK found that poor HL was associated with lower QoL scores (i.e. physical, psychological, social relationships and environment) . In light of these conflicting results, it seems possible that the relationship between HL and QoL depends on certain aspects such as specific chronic diseases, cultural characteristics or other aspects of QoL.…”
Section: Discussionmentioning
confidence: 93%